Public Transport Service Optimization and System Integration - Fang, Ke; Zimmerman, Samuel (World Bank, Washington, DC, 2015)
Public transport has the most customer appeal and is most efficient when it is planned and operated as a seamless, integrated system. This is particularly important in urban environments in fast growing economies such as China and India, where public transport must increasingly compete with private vehicles which offer door-to-door, one seat travel irrespective of time of day or day of the week. International experience suggests that public transport planners must recognize two integration dimensions: (a) integration among all modes and routes comprising the multi-modal public transport network, (b) integration of the physical and operational elements or each respective mode and service, e.g., metro or bus. Successful integration in both dimensions will provide a more customer-friendly experience and make public transport more efficient and cost-effective. This will help maximize public transport ridership and revenue, increase customer satisfaction, reduce costs and subsidies and general environmental, social and economic benefits for the investment.